5^27:25^13+5^20+5^1·[625:5^4+5^2:(5·5^2-120^1)]
Răspunsuri la întrebare
Răspuns de
0
=5^27 : (5^2)^13+5^20+5^1•[5^4:5^4+5^2:(5•5^2-120)]
= 5^27:5^26+5^20+5•[1+5^2÷(5^3-120)]
= 5^1+5^20+5•[1+5^2:(125-120)]
= 5^1+5^20+5•(1+5^2:5)
= 5^1+5^20+5•(1+5)
= 5+5^20+5•6
= 5+5^20+30
= 35+5^20
= 5^27:5^26+5^20+5•[1+5^2÷(5^3-120)]
= 5^1+5^20+5•[1+5^2:(125-120)]
= 5^1+5^20+5•(1+5^2:5)
= 5^1+5^20+5•(1+5)
= 5+5^20+5•6
= 5+5^20+30
= 35+5^20
Alte întrebări interesante
Limba română,
9 ani în urmă
Informatică,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Chimie,
9 ani în urmă